Method for preparing flaky single-crystal Sr2MgSi2O7: Eu < 2 + >, Dy < 3 + > long-afterglow powder material by molten salt method

The prepared sheet-shaped single crystal Sr2MgSi2O7:Eu2+, Dy3+ long afterglow powder material is solved by the molten salt method, which solves the problems of high energy consumption, long time and low yield in the existing technology, realizes high efficiency and low cost preparation of the material, and improves the afterglow time and thermal stability of the material.

CN119900070APending Publication Date: 2025-04-29HANGZHOU DIANZI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411962283.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing long afterglow material preparation methods have problems such as high energy consumption, long time, low yield, easy introduction of impurities and environmental pollution, and it is difficult to meet the high efficiency, low cost and high performance requirements of the material.

Method used

A sheet-shaped single crystal Sr2MgSi2O7:Eu2+, Dy3+ long afterglow powder material was prepared by molten salt method. By mixing the precursor with molten salt, calcining at 700-1000°C, and passing a reducing gas, washing and drying it naturally, a single crystal sheet-shaped material was obtained.

Benefits of technology

It effectively reduces the synthesis temperature and time and reduces the preparation cost. The prepared materials have a regular single-crystalline structure, uniform size, strong crystallinity, and the afterglow time is up to 24 hours, and the thermal stability is also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900070A_ABST
    Figure CN119900070A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a flaky single-crystal Sr2MgSi2O7: Eu < 2 + >, Dy < 3 + > long-afterglow powder material by a molten salt method. The preparation method comprises the following steps: firstly, preparing a precursor, mixing the precursor with molten salt according to a ratio of 1: 1, uniformly grinding, sintering for 2 hours at 800 DEG C in a reducing atmosphere, washing with deionized water after heat preservation is finished, and drying to obtain the flaky single crystal material. According to the method, the reaction temperature is effectively reduced, the reaction time is shortened, and the morphology of the product can be controlled by selecting proper experimental conditions. The prepared single-crystal Sr2MgSi2O7: Eu < 2 + >, Dy < 3 + > long-afterglow material is in a regular sheet shape, is uniform in size, and has the afterglow time as long as 24 h under 365 nm excitation. Compared with reported Sr2MgSi2O7: Eu < 2 + >, Dy < 3 + > materials, the afterglow performance and the thermal stability of the material are remarkably improved, and the method provides a new research thought for subsequent research and development of long afterglow materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of long afterglow luminescent material preparation. Specifically, it relates to a method for preparing a sheet-shaped single crystal Sr2MgSi2O7:Eu by a molten salt method. 2+ ,Dy 3+ Method for long afterglow powder material. Technical Background

[0002] In the rapid development of modern optoelectronic devices and display technologies, long afterglow materials have attracted much attention due to their unique properties in light storage and luminescence. These materials store energy when excited by light and release energy in the form of light after the excitation stops. They are widely used in cutting-edge scientific application fields such as biological imaging, information storage, medical diagnosis, and energy engineering. However, with the widespread application of long afterglow materials, complex application conditions have also put forward new requirements for the synthesis method, micromorphology, and optical properties of long afterglow materials.

[0003] At present, the common preparation methods of long afterglow materials mainly include high temperature solid phase method, hydrothermal method, sol-gel method and co-precipitation method. High temperature solid phase method can usually effectively improve the crystallinity and luminescence intensity of the material, but it requires high energy consumption and a long time, and the prepared powder material is large in size and the morphology is uncontrollable; the hydrothermal method can effectively control the particle size and morphology of the material, but the yield is low and the scope of application is small; the sol-gel method has a long cycle and is prone to environmental pollution; the co-precipitation method has a low yield, and impurities are easily introduced during the reaction, affecting the performance of the material. These limitations have prompted researchers to seek new synthesis methods to optimize the preparation process of long afterglow materials.

[0004] Among many long afterglow materials, Sr2MgSi2O7:Eu 2+ ,Dy 3+ This silicate material has attracted much attention due to its excellent optical properties. It exhibits bright fluorescence and excellent afterglow performance, has good luminescence properties and chemical stability, and has therefore been widely studied. C.Xu et al. successfully synthesized Sr2MgSi2O7:Eu by solid phase sintering at 1350°C. 2+ ,Dy 3+ Long afterglow phosphor, the longest afterglow time can reach 13.5h. HYWu et al. synthesized bulk Sr2MgSi2O7:Eu at 1400℃ 2+ ,Dy 3+ , the longest afterglow time can reach 12h. 2+ ,Dy 3+ The afterglow time can reach 19h. These studies show that the preparation method has a significant effect on the luminous intensity and afterglow time of long afterglow materials.2+ ,Dy 3+ The research and development of new long afterglow materials has important theoretical value and practical significance. Summary of the invention

[0005] The present invention aims to overcome the defects of the prior art and provide a molten salt method for preparing sheet single crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ The method for preparing long afterglow powder material can effectively reduce the synthesis temperature and preparation cost, and the prepared Sr2MgSi2O7:Eu 2+ ,Dy 3+ The long afterglow material is a single crystal crystalline structure with regular morphology, uniform size and strong crystallinity.

[0006] To achieve the above object, the present invention provides a molten salt method for preparing a sheet single crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ The method for producing a long afterglow powder material comprises the following steps:

[0007] S1 prepares the precursor;

[0008] S2: Mix the above precursor with molten salt, add ethanol and grind evenly, calcine at 700-1000℃ for 0.5-5h, continuously introduce reducing gas during calcination to maintain reducing atmosphere, and take out the sample after naturally cooling to room temperature;

[0009] S3 washes the sample obtained in S2 to remove the mixed molten salt, and then dries to obtain a single crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ .

[0010] Preferably, S1 prepares the precursor, specifically comprising the following steps:

[0011] Step 1: Dissolve the raw materials SrCl2·6H2O, MgCl2·6H2O, Eu(NO3)3·6H2O, and Dy(NO3)3·6H2O in deionized water to prepare a solution; 2+ ,Dy 3+ The Sr, Mg, Si, Eu, and Dy elements are mixed in a stoichiometric ratio to obtain a mixed solution, and then TEOS and alcohol are mixed in a ratio of 1:1 and added to the mixed solution, and a proper amount of dilute HNO3 is added to adjust the pH of the solution to obtain solution A;

[0012] Step 2: Heat solution A in a 75°C water bath for 2 hours. After the water bath, dry it at 120°C for 12 hours to obtain a white solid powder. Calcine the powder at 500°C for 150 minutes to obtain a precursor.

[0013] Preferably, in S2, the precursor and the molten salt are mixed in a mass ratio of 1:1; and the heating rate of calcination is 5°C / min.

[0014] Preferably, an appropriate amount of dilute HNO3 is added to adjust the pH of the solution to 0.1-4.5.

[0015] Preferably, the molten salt is KCl or NaCl.

[0016] Preferably, in S3, the drying temperature is 60°C.

[0017] Preferably, when the precursor and the molten salt are mixed in S2, the mass ratio of the precursor to the molten salt is 1:X, wherein 0.5≤X≤5.

[0018] Preferably, in S2, the reducing gas is a mixed gas containing hydrogen.

[0019] The present invention has the following excellent effects:

[0020] 1. The operation of the present invention is simple, which effectively reduces the reaction temperature, shortens the reaction time, reduces the test cost, and makes the material synthesis more efficient.

[0021] 2. The present invention can prepare a single crystal long afterglow phosphor with regular morphology and uniform size by selecting appropriate experimental conditions, thereby achieving effective regulation of the product morphology.

[0022] 3. Sr2MgSi2O7:Eu prepared by the present invention 2+ ,Dy 3+ The long afterglow phosphor has good crystallinity. Experimental measurements show that the afterglow time is as long as 24 hours. Compared with existing commercial phosphors, its thermal stability is also improved to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Example 3 of the present invention is to prepare Sr2MgSi2O7:Eu based on the molten salt method 2+ ,Dy 3+ XRD pattern of powder.

[0024] Figure 2 for Figure 1 Sr2MgSi2O7:Eu 2+ ,Dy 3+ SEM image of the powder.

[0025] Figure 3 for Figure 1 Sr2MgSi2O7:Eu 2+ ,Dy 3+ TEM image of the powder.

[0026] Figure 4Sr2MgSi2O7:Eu prepared in Example 3 2+ ,Dy 3+ Afterglow decay curve of powder.

[0027] Figure 5 For the sample of Example 3 and commercial Sr2MgSi2O7:Eu 2+ ,Dy 3+ Powder pl intensity variation curve at different V / S. DETAILED DESCRIPTION

[0028] The present invention is analyzed in detail below in conjunction with specific embodiments. The following embodiments are intended to illustrate the present invention, and any improvements and changes made on the basis of the present invention are within the protection scope of the present invention.

[0029] Example 1

[0030] Step 1: Dissolve SrCl2·6H2O, MgCl2·6H2O, Eu(NO3)3·6H2O, Dy(NO3)3·6H2O and other raw materials in 100ml of deionized water to prepare a 0.1mol / L solution. Take out and mix the solution according to a certain stoichiometric ratio, then add TEOS and alcohol in a 1:1 ratio to the mixture, and add an appropriate amount of dilute HNO3 to adjust the pH of the solution to ≈ 1.

[0031] Step 2: Heat the mixed solution in step 1 in a water bath at 75°C for 2 hours. After the water bath ends, dry it at 120°C for 12 hours to obtain a white solid powder. Calcine the powder at 500°C for 150 minutes to obtain a precursor.

[0032] Step 3: Take 2g of the above precursor and mix it with KCl in a mass ratio of 1:1, add ethanol and grind for 30min. After grinding evenly, place it in a crucible and put it into a muffle furnace and calcine it at 700℃ for 2h. The heating rate is 5℃ / min. During the calcination process, reducing gas is continuously introduced to maintain a reducing atmosphere. After naturally cooling to room temperature, take out the sample.

[0033] Step 4: Wash the sample obtained in step 3 with deionized water to remove the mixed KCl, filter it, and dry it at 60°C to obtain a single crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ sample.

[0034] Example 2

[0035] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being ground evenly, it was placed in a crucible and placed in a muffle furnace for calcination at 750°C for 2 hours, with a heating rate of 5°C / min. During the calcination process, a reducing gas was continuously introduced to maintain a reducing atmosphere, and the sample was taken out after naturally cooling to room temperature. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0036] Example 3

[0037] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being evenly ground, it was placed in a crucible and calcined at 800°C in a muffle furnace for 2 hours at a heating rate of 5°C / min. During the calcination process, a reducing gas was continuously introduced to maintain a reducing atmosphere. After naturally cooling to room temperature, the sample was taken out. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0038] See attached Figure 1 Sr2MgSi2O7:Eu prepared according to the scheme of this embodiment 2+ ,Dy 3+ The X-ray diffraction pattern of the sample shows that the crystal phase of the prepared material is Sr2MgSi2O7. Figure 2 and attached Figure 3 The scanning electron microscope (SEM) and transmission electron microscope (TEM) images of the sample prepared in Example 3 show that this method can successfully prepare single-crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ The afterglow decay curve of the sample was tested under 365nm ultraviolet light excitation by a fluorescence spectrometer, as shown in the attached figure. Figure 4 As shown in Figure 2, the longest afterglow that can be monitored by this sample can reach 24h. When the temperature rises from 303K to 423K, the pl intensity of the sample in Example 3 drops to 50% of the initial value, while the commercial Sr2MgSi2O7:Eu 2+ ,Dy 3+ The pl intensity of the sample has a greater change, falling to 25% of the initial value (see Figure 5 ), which shows that the molten salt method effectively improves the thermal stability of the material.

[0039] Example 4

[0040] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being ground evenly, it was placed in a crucible and placed in a muffle furnace for calcination at 850°C for 2 hours, with a heating rate of 5°C / min. During the calcination process, a reducing gas was continuously introduced to maintain a reducing atmosphere, and the sample was taken out after naturally cooling to room temperature. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0041] Example 5

[0042] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being ground evenly, it was placed in a crucible and calcined at 900°C in a muffle furnace for 2 hours at a heating rate of 5°C / min. During the calcination process, a reducing gas was continuously introduced to maintain a reducing atmosphere. After naturally cooling to room temperature, the sample was taken out. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0043] Example 6

[0044] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being evenly ground, it was placed in a crucible and placed in a muffle furnace for calcination at 950°C for 2 hours, with a heating rate of 5°C / min. During the calcination process, a reducing gas was continuously introduced to maintain a reducing atmosphere, and the sample was taken out after naturally cooling to room temperature. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0045] Example 7

[0046] The precursor in Example 1 was mixed with KCl at a mass ratio of 1:1, ethanol was added and fully ground for 30 minutes, and after being evenly ground, it was placed in a crucible and calcined at 1000°C in a muffle furnace for 2 hours at a heating rate of 5°C / min. During the calcination process, reducing gas was continuously introduced to maintain a reducing atmosphere. After naturally cooling to room temperature, the sample was taken out. The sample was washed with deionized water to remove the mixed KCl, filtered, and dried at 60°C to obtain the target product.

[0047] Comparative Example 1

[0048] This embodiment is the same as Embodiment 3 except that the molten salt used is NaCl. After calcination, the sample is washed with deionized water to remove the mixed NaCl, filtered, and dried at 60°C to obtain the target product. Under the excitation of 365nm ultraviolet light by a fluorescence spectrometer, the longest afterglow time that can be monitored by the phosphor can reach 18h.

[0049] Comparative Example 2

[0050] This embodiment is the same as Embodiment 3 except that the molten salt used is K2CO3. After calcination, the sample is washed with deionized water to remove the mixed K2CO3, filtered, and dried at 60°C to obtain the target product. Under the excitation of 365nm ultraviolet light by a fluorescence spectrometer, the longest afterglow time that can be monitored by the phosphor can reach 16.5h.

[0051] Comparative Example 3

[0052] This embodiment is the same as Embodiment 3 except that the molten salt used is Na2CO3. After calcination, the sample is washed with deionized water to remove the mixed Na2CO3, filtered, and dried at 60°C to obtain the target product. Under the excitation of 365nm ultraviolet light by a fluorescence spectrometer, the longest afterglow time that can be monitored by the phosphor can reach 12h.

[0053] Comparative Example 4

[0054] This embodiment is the same as Embodiment 3 except that the molten salt used is KF. After calcination, the sample is washed with deionized water to remove the mixed KF, filtered, and dried at 60°C to obtain the target product. Under the excitation of 365nm ultraviolet light by a fluorescence spectrometer, the longest afterglow time that can be monitored by the phosphor can reach 7h.

[0055] Comparative Example 5

[0056] This embodiment is the same as Embodiment 3 except that the molten salt used is NaF. After calcination, the sample is washed with deionized water to remove the mixed NaF, filtered, and dried at 60°C to obtain the target product. Under the excitation of 365nm ultraviolet light by a fluorescence spectrometer, the longest afterglow time that can be monitored by the phosphor can reach 3h.

[0057] The above descriptions are only some specific implementation methods of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by any person familiar with the art within the technical scope disclosed in the present invention should be covered within the protection scope of the present invention.

Claims

1. Preparation of flake single crystal Sr2MgSi2O7:Eu by molten salt method 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: The following steps are involved: S1 prepares the precursor; S2: Mix the above precursor with molten salt, add ethanol and grind evenly, calcine at 700-1000℃ for 0.5-5h, continuously introduce reducing gas during calcination to maintain reducing atmosphere, and take out the sample after naturally cooling to room temperature; S3 washes the sample obtained in S2 to remove the mixed molten salt, and then dries to obtain a single crystal Sr2MgSi2O7:Eu 2+ ,Dy 3+ .

2. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 1 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: S1 prepares the precursor, specifically comprising the following steps: Step 1: Dissolve the raw materials SrCl2·6H2O, MgCl2·6H2O, Eu(NO3)3·6H2O, and Dy(NO3)3·6H2O in deionized water to prepare a solution; 2+ ,Dy 3+ The Sr, Mg, Si, Eu, and Dy elements are mixed in a chemical composition ratio to obtain a mixed solution, and then TEOS and alcohol are mixed in a ratio of 1:1 and added to the mixed solution, and a proper amount of dilute HNO3 is added to adjust the pH of the solution to obtain solution A; Step 2: Heat solution A in a 75°C water bath for 2 hours. After the water bath ends, dry it at 120°C for 12 hours to obtain a white solid powder. Calcine the powder at 500°C for 150 minutes to obtain a precursor.

3. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 1 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: In S2, the precursor and the molten salt are mixed in a mass ratio of 1:1; the heating rate of calcination is 5°C / min.

4. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 2 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: Add appropriate amount of dilute HNO3 to adjust the pH of the solution to 0.1-4.

5.

5. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 3 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: The molten salt is KCl or NaCl.

6. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 3 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: In S3, the drying temperature is 60°C.

7. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 3 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: When the precursor and the molten salt are mixed in S2, the mass ratio of the precursor to the molten salt is 1:X, where 0.5≤X≤5.

8. Preparation of sheet single crystal Sr2MgSi2O7:Eu by molten salt method as claimed in claim 1 2+ ,Dy 3+ The method for producing a long afterglow powder material is characterized in that: In S2, the reducing gas is a mixed gas containing hydrogen.